The Use of Historical Sites in The City of Palu as Objects of Historical Research and Learning Based on Digital History - Suyuti; Hasan; Wilman D. Lumangino (Kirana Publisher (KNPub), 2023)
Utilizing historical sites for object research and teaching history through digital history are crucial since historical sites are one of the primary sources of historical information and may describe events in more detail for the benefit of participant education. As the capital of Central Sulawesi Province, Palu City offers a number of historical sites that can be used as research subjects. Studying history in Palu offers a good balance between the site's content and what is taught in high school curricula. One of the guiding principles of implementation is the use of historical sites as sources for learning and objects for study in a supportive curriculum. That issue became the rationale for why Palu's historical sites are important for research and how much of them may be used as sources. Look it over. Examine This goal is to understand the significance of Palu's historical landmarks for object learning contexts and utilization tactics in learning-based digital history. Approach investigation This method is descriptive and qualitative. Fieldwork observation, surveys, interviews, and excavations were used to gather data, along with a variety of documents from pertinent publications and journals. Outer aim from the analysis of results This is how a number of locations' legacies might be used for object study and historical education among participants in material change and sustainability. Learning digital history through an internal site use approach can be accomplished in four steps: 1) introduction, 2) observation, 3) discussion, and 4) findings. Similar to level readiness technology (TKT), historical sites are anticipated to be used as study objects and for teaching history based on digital media. The purpose of this is to introduce participants to the site while educating them, and to disseminate information to the public through digital media. The public will find Palu City's historical landmarks more and more fascinating, making it possible for them to become a destination for integrated historical tours.